Multigene phylogenetic data place monoraphid diatoms Schizostauron and Astartiella along with other fistula‐bearing genera in the Stauroneidaceae1. Issue 5 (23rd July 2021) - Górecka, Ewa; Ashworth, Matt P.; Davidovich, Nikolai; Davidovich, Olga; Dąbek, Przemysław; Sabir, Jamal S.M.; Witkowski, Andrzej
Abstract : Presented here are new insights into the marine monoraphid diatom genera Schizostauron and Astartiella, based on molecular and morphological data, including descriptions of new species. Although no unambiguous morphological synapomorphies between the two genera are currently recognized, they are closely related by DNA sequence data. Heterovalvate frustules of Schizostauron are characterized by a bifid stauros on the raphe‐bearing valve and intricate areolate occlusions on the sternum valve. In Astartiella, the raphe‐bearing valve is characterized by a process resembling a fistula by morphology, while the sternum valve presents a particular striation pattern. Observations by light and electron microscopy were made, along with a molecular phylogenetic analysis using a three‐gene (SSU, rbc L, and psb C) concatenated dataset. Three new Schizostauron species are described ( S. kajotkei, S . rawaii, S. papilliareae ), and two new combinations proposed ( S. citronella and S. trachyderma ) for species that were previously included either in Achnanthes and Cocconeis, respectively. Likewise, six new species of Astartiella ( A. almalikii, A. bornmanii, A. chunlianlii, A . marksii, A. persica, and A . wangii ) are described. Molecular results exclude Schizostauron and Astartiella from three clades of exclusively monoraphid diatoms, the Achnanthaceae, Cocconeidaceae, and Achnanthidiaceae, instead placing them in the Stauroneidaceae. Morphological features of Schizostauron and Astartiella, such as the stauros, fistula, and coaxial internal proximal raphe endings, are found in other genera in this clade, whereas the only common feature with monoraphid diatoms as whole group is the heterovalvy of frustules.